Pancreas divisum and recurrent pancreatitis: long-term results of minor papilla sphincterotomy. (4th March 2019) - Tringali, Andrea; Voiosu, Theodor; Schepis, Tommaso; Landi, Rosario; Perri, Vincenzo; Bove, Vincenzo; Voiosu, Andrei Mihai; Costamagna, Guido
Abstract: Background and aims: Pancreas divisum (PD) is the most common congenital variant of the pancreatic ductal system and a potential cause of acute recurrent pancreatitis (ARP). Endoscopic therapy is a therapeutic option for symptomatic PD, but there is limited data on long-term results. We aimed to assess the effect of minor papilla endoscopic sphincterotomy (MiES) in the setting of ARP in patients with PD. Methods: Consecutive patients treated by MiES were included. Clinical data, including gender, age, smoking and drinking habits, number of episodes of acute pancreatitis (AP) as well as technical data pertaining to the endoscopic therapy were reviewed. Patients available for follow-up were contacted to assess the long-term impact of MiES using the Patient's Global Impression of Change (PGIC) questionnaire. Results: A total of 138 patients with PD including 77 patients with ARP underwent MiES; 48 patients were available for long-term follow-up using the PGIC score, with a mean follow-up period of 9.7 years. Procedure-related adverse events developed in 10 cases (12.9%): 5 post-MiES delayed bleeding and 5 mild pancreatitis. MiES was clinically successful in 35 patients (72.9%) who did not experience any more episodes of AP. Improvement in quality of life (PGIC ≥6) occurred in 41/48 patients (85.4%). On multivariate analysis, stenosis of the MiES was the only predictive factor for increased risk of recurrent pancreatitis after initial therapy. Conclusion: MiES resulted an efficient treatment for ARP in patients with PD with clinical benefit, patient satisfaction and improved quality of life even at long-term follow-up.